2020
DOI: 10.1097/md.0000000000019847
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical effects of foraminoplasty of different areas under lumbar percutaneous endoscopy on intervertebral discs

Abstract: Background: We set out to evaluate the biomechanical influence of foraminoplasty on intervertebral discs in different areas under lumber percutaneous endoscopy through the use of a three-dimensional finite element. Methods: We established a normal 3D finite element mode of L3–5, using simulate lumbar percutaneous endoscopy by carrying out cylindrical excision of a bone whose diameter was 7.5 mm on the L5 superior articular process and the L4 inferior ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…However, the stress of L4-5 disks increased significantly after molding, with an increase of less than 9% in Group B and 26% in Group C, while the disk stress of the DE group could increase up to a maximum of 44%. These findings were consistent with those observed by Xie et al [ 23 ] and Li et al [ 27 ], where simple ventral SAP resection had a minimal effect on disk stress, but extended ventral resection or SAP shoulder resection could affect the overall bearing of the facet, thus increasing the disk stress of L45. This increase in disk stress may result in postoperative L45 disk stress concentration, leading to possible recurrence of disk herniation or accelerated space degeneration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the stress of L4-5 disks increased significantly after molding, with an increase of less than 9% in Group B and 26% in Group C, while the disk stress of the DE group could increase up to a maximum of 44%. These findings were consistent with those observed by Xie et al [ 23 ] and Li et al [ 27 ], where simple ventral SAP resection had a minimal effect on disk stress, but extended ventral resection or SAP shoulder resection could affect the overall bearing of the facet, thus increasing the disk stress of L45. This increase in disk stress may result in postoperative L45 disk stress concentration, leading to possible recurrence of disk herniation or accelerated space degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have reported the role of the lumbar zygapophysial articular cartilage plays in maintaining the overall stability of the lumbar spine and protecting the annulus fibrosus [ 22 , 23 ]. Spine surgeons traditionally believed that varying types of facet facetectomy have little impact on postoperative stability [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our volumetric analysis, grounded in a precise and replicable formula, offers a framework for integrating quantitative imaging assessments into the diagnostic process for lumbar spinal disorders. By establishing normative data for lumbar foraminal volumes, our study paves the way for developing diagnostic criteria and thresholds that can be applied in clinical settings to differentiate normal anatomical variations from clinically significant stenosis ( Figure 4 ) [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%